EFFECT OF HIJRAH INTENTION, ISLAMIC BANK SERVICE QUALITY, AND ISLAMIC BRANDING ON LOYALTY IN THE USE OF SHARIA DIGITAL BANKING WITH SATISFACTION AS AN INTERVENING VARIABEL (Case Study BTN Syariah KCP Pekalongan) - Nunung Setiani; Fetria Eka Yudiana (Imara: JURNAL RISET EKONOMI ISLAM, 2022)
This study was conducted to determine the effect of Hijrah Intention, Islamic Bank Service Quality, and Islamic Branding on Loyalty in the Use of Sharia Digital Banking. The method of collecting data is through a questionnaire distributed to the Bank's customers. The sample used in this study were 95 respondents with the non-probability sampling technique. This analysis includes instrument test, statistical test, classical assumption test, and path analysis. Based on the results of the study, it showed that Hijrah Intention had a negative and insignificant effect on customer satisfaction. Meanwhile, Islamic Bank Service Quality and Islamic Branding have a positive and significant effect on customer satisfaction. Hijrah Intention, Islamic Bank Service Quality, Islamic Branding have a positive and significant effect on customer loyalty. Customer satisfaction is not able to mediate Hijrah Intention to loyalty. Meanwhile, Islamic Bank Service Quality and Islamic Branding on customer loyalty can be mediated by customer satisfaction.